Structure and time behavior of arc cathode spots; Proceedings of the 20th International Symposium on Discharges and Electrical Insulation in Vacuum, Tours, july 1-5, 2002 - Barengolts S. A. (2002, 2002)
В фонде НТБ ТПУ отсутствует